2011
DOI: 10.1039/c0ee00634c
|View full text |Cite
|
Sign up to set email alerts
|

Optimal process design for the polygeneration of SNG, power and heat by hydrothermal gasification of waste biomass: Process optimisation for selected substrates

Abstract: Based on a previously developed thermo-economic process model, this paper presents a detailed design study for the polygeneration of Synthetic Natural Gas (SNG), power and heat by catalytic hydrothermal gasification of biomass and biomass wastes in supercritical water. Using multi-objective optimisation techniques, the thermodynamic and thermo-economic performances of all candidate configurations from a general process superstructure are optimised with respect to SNG and electricity cogeneration and its associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…Here, both of the authors investigated the energy efficiencies of wood gasification processes. The results of Gassner et al [28] showed that the overall energy efficiency for a wood gasification process targeting the production of synthetic natural gas (SNG) in SCWG is 70%. The overall energy efficiency is given in Equation (1) …”
Section: Gasificationmentioning
confidence: 99%
See 3 more Smart Citations
“…Here, both of the authors investigated the energy efficiencies of wood gasification processes. The results of Gassner et al [28] showed that the overall energy efficiency for a wood gasification process targeting the production of synthetic natural gas (SNG) in SCWG is 70%. The overall energy efficiency is given in Equation (1) …”
Section: Gasificationmentioning
confidence: 99%
“…Figure 8 shows the comparison of supercritical water gasification (SCWG) with the other biomass conversion routes on heat utilization efficiency basis. Another comparison between conventional gasification and SCWG can be made based on the works of Gassner et al [28] and van der Meijden et al [29]. Here, both of the authors investigated the energy efficiencies of wood gasification processes.…”
Section: Gasificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Catalytic SCWG allows the production of SNG from biomass without prior drying (water content ¼ 50%e90%) at high chemical energy conversion efficiencies of up to 70%e77% [10,11]. Such high energy conversion efficiencies are possible because at supercritical pressure the specific and latent heat demand of water is strongly decreased, thus being a promising biofuel pathway for feedstocks with high water content like microalgae [12].…”
Section: Introductionmentioning
confidence: 99%